Analysis Of The Effect Of Supervision, Leadership, And Compensation On Employee Performance At The SUMUT DPRD Office - Fadillah, M. Iqbal; Yanti, Eli Delvi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to find the effect of supervision, leadership and compensation on employee performance at the North Sumatra DPRD Office. Does leadership partially have a positive and significant effect on employee performance at the North Sumatra DPRD Office. Does compensation partially have a positive and significant effect on employee performance at the North Sumatra DPRD Office. Do supervision, leadership and compensation simultaneously have a positive and significant effect on employee performance at the North Sumatra DPRD Office. The research method is causal associative research with the help of the SPSS Version 25 programme. This research uses multiple linear regression. The population in this study were 80 respondents. The sample in this study were 80 respondents. Primary data collection using a questionnaire. The results showed that supervision partially had a positive and significant effect on employee performance at the North Sumatra DPRD Office. Leadership partially has a positive and significant effect on employee performance at the North Sumatra DPRD Office. Compensation partially has a positive and significant effect on employee performance at the North Sumatra DPRD Office. Supervision, leadership and compensation simultaneously have a positive and significant effect on employee performance at the North Sumatra DPRD Office.